Financial Risk Management Impact on Islamic Bank Performance Mediated by Earnings Quality Moderated Governance Literacy - Heni Purwantini; Victor Prasetya; Mutia Pamikatsih; Muhammad Shahid Khan (Universitas Tidar, 2026)
This study examines the influence of financial risk management on the performance of Islamic banks with earnings quality as a mediating factor and governance literacy as a moderating factor. The research is grounded on the phenomenon whereby the need for financial management and accounting integration for explaining the sustainable performance of Islamic banking institutions is high. A quantitative approach was utilized whereby primary data were collected from Islamic commercial banks and Islamic rural banks throughout the archipelago of Indonesia. The collected data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate the direct and indirect relationships of the variables. The study established that financial risk management positively and significantly influences the performance of Islamic banks. Moreover, it was established that financial risk management and performance relationship is positively and significantly mediated by earnings quality, indicating that with better financial reporting quality, performance is enhanced as a result of effective risk management. However, governance literacy does not significantly moderate the relationship between financial risk management and performance. The results imply that the quality of internal financial control systems and the accounting system is more critical to driving performance than governance knowledge. The research adds to the body of knowledge by advancing risk management theory by incorporating accounting-based mechanisms, providing empirical feedback to bank managers and regulators aiming to reinforce the financial sustainability of Islamic banking institutions.